Design and fabrication of young coconut slicer machine / Hafiy Harith Hizam - Hizam, Hafiy Harith (2024)
Despite the high sale rate, almost all vendors extract coconut water in the old- fashioned manner. They cut a hole in the fragile coconut's top with a sharp knife. To make the hole, it takes a lot of expertise and work and is quite dangerous for beginners. Because it takes a lot of work, it has a lower efficiency. Also causes the seller's shoulders ache when trying to serve it in a large quantity. Based on that statement, the coconut slicer will be designed and fabricated in this project. The project objective is to design, analysis and fabricate the coconut slicer machine. However, this project will be limited to young coconut and to extract its juice. For FYP1, the plan to complete this machine consisted of design stage and analysis by using SolidWork software. Meanwhile for FYP2, fabrication process will be conducted. The main element of this project will be aluminium, linear actuator and custom mechanical component. The machine size to be approximately 300mm x 300mm x 500mm.